2017
DOI: 10.1002/bip.22988
|View full text |Cite
|
Sign up to set email alerts
|

Spliced analogues of trypsin inhibitor SFTI‐1 and their application for tracing proteolysis and delivery of cargos inside the cells

Abstract: A series of analogues of trypsin inhibitor SFTI-1 were designed and synthesized to monitor peptide splicing. In the middle part of the SFTI-1 analogues, which is released upon incubation with proteinase, the RGD sequence or an acceptor of fluorescence for FRET was introduced. The results of studies with trypsin confirmed that the designed analogues underwent peptide splicing. Furthermore, we showed that a FRET displaying SFTI-1 analogue was internalized into the HaCaT keratinocytes, where it was degraded. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(34 reference statements)
0
5
1
Order By: Relevance
“…As shown by HPLC and MS analysis, the conjugate was not present in the reaction mixture after 1 h of incubation with trypsin (see Figure S2 in Supporting Information). These results significantly differ from our previous stability studies of trypsin inhibitor SFTI-1 and its analogues. , We have shown that intramolecular disulfide bonds in SFTI-1 and its analogues were not reduced in serum, and their presence in molecules significantly increased proteolytic resistance of these compounds …”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…As shown by HPLC and MS analysis, the conjugate was not present in the reaction mixture after 1 h of incubation with trypsin (see Figure S2 in Supporting Information). These results significantly differ from our previous stability studies of trypsin inhibitor SFTI-1 and its analogues. , We have shown that intramolecular disulfide bonds in SFTI-1 and its analogues were not reduced in serum, and their presence in molecules significantly increased proteolytic resistance of these compounds …”
Section: Resultscontrasting
confidence: 99%
“…These results significantly differ from our previous stability studies of trypsin inhibitor SFTI-1 and its analogues. 17,18 We have shown that intramolecular disulfide bonds in SFTI-1 and its analogues were not reduced in serum, and their presence in molecules significantly increased proteolytic resistance of these compounds. 18 Conformational Analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[53] Human serum from male plasma (Sigma-Aldrich, Germany) was prepared for the assay as described. [53] Human serum from male plasma (Sigma-Aldrich, Germany) was prepared for the assay as described.…”
Section: Assay To Determine the Stability In Serummentioning
confidence: 99%